2022
DOI: 10.1002/ecy.3680
|View full text |Cite
|
Sign up to set email alerts
|

Decline effects are rare in ecology

Abstract: The scientific evidence base on any given topic changes over time as more studies are published. Currently, there is widespread concern about nonrandom, directional changes over time in the scientific evidence base associated with many topics. In particular, if studies finding large effects (e.g., large differences between treatment and control means) tend to get published quickly, while small effects tend to get published slowly, the net result will be a decrease over time in the estimated magnitude of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(69 citation statements)
references
References 40 publications
6
61
2
Order By: Relevance
“…The observed power to determine a decline effect in the current set of 87 meta-analyses was considerably low (median = 13%). This low power was similar to that observed in another much larger survey of 464 ecological meta-analyses (median = 17%; [68,69]). Importantly, our second-order meta-analysis have found a statistically significant and homogeneous effect (Figure 6A), corroborating that decline effects are common in both subfields previously explored (status signalling: [70], plant and insect biodiversity: [17,71] and ocean acidification: [72]) and general fields of ecology and evolutionary biology [12,68].…”
Section: Discussionsupporting
confidence: 85%
“…The observed power to determine a decline effect in the current set of 87 meta-analyses was considerably low (median = 13%). This low power was similar to that observed in another much larger survey of 464 ecological meta-analyses (median = 17%; [68,69]). Importantly, our second-order meta-analysis have found a statistically significant and homogeneous effect (Figure 6A), corroborating that decline effects are common in both subfields previously explored (status signalling: [70], plant and insect biodiversity: [17,71] and ocean acidification: [72]) and general fields of ecology and evolutionary biology [12,68].…”
Section: Discussionsupporting
confidence: 85%
“…This assumption usually holds but not always. Approximately 3%–5% of ecological meta‐analyses exhibit true directional trends in mean effect size over time as more and more studies are published (Costello & Fox, 2022 ). Those directional trends arose because primary research studies were published in nonrandom order with respect to the effect sizes they reported, usually with larger‐magnitude effect sizes being published earlier (Costello & Fox, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, even meta‐analytic estimates of mean effect size remain at least somewhat imprecise, particularly estimates from small meta‐analyses. The median ecological meta‐analysis comprises just 64 effect sizes from just 24 primary research studies (information extracted from data compiled by Costello & Fox, 2022 ). Just by chance, small meta‐analyses are more likely than large ones to produce imprecise, large‐magnitude estimates of mean effect size.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations